Microbiological Quality of Meat and Swabs from Contact Surface in Butcher Shops in Debre Berhan, Ethiopia - Tefera Atlabachew; Jermen Mamo (Journal of Food Quality)
Food-borne pathogens are the primary source of infection in developing countries. The widespread practice of raw beef consumption was a potential cause of food-borne diseases in Ethiopia. Hence, this study was initiated to assess the microbiological quality of fresh meat samples from butcher shops in Debre Berhan. Fresh meat samples and swab samples from contact surfaces were collected from butcher shops for microbial analysis, following standard methods. The study revealed that the mean microbial counts of morning samples for total aerobic mesophilic, Staphylococci, Enterobacteriaceae, total coliform, fecal coliform, aerobic spore formers, and yeasts and molds of the butcher shops were 5.31, 4.24, 4.47, 4.79, 4.74, 3.77, and 5.0 log cfu/g, respectively. The mean microbial counts from the afternoon sample for total aerobic mesophilic, Staphylococci, Enterobacteriaceae, total coliform, fecal coliform, aerobic spore formers, and yeasts and molds of the butcher shops were 5.47, 4.78, 4.84, 4.88, 4.94, 5.15, and 5.07 log cfu/g, respectively. A higher microbial load was found from the meat sample collected in the afternoon. The mean microbial counts of total aerobic mesophilic, Staphylococci, Enterobacteriaceae, total coliform, fecal coliform, aerobic spore formers, and yeasts and molds from swabs of the contact surface were 4.17, 3.98, 4.08, 3.96, 3.86, 3.80, and 3.92 log cfu/cm2, respectively. Further characterization of the aerobic mesophilic flora indicated a dominance by Enterobacteriaceae (36%) followed by Staphylococci spp. (24%) and Bacillus spp. (19%). The prevalence of S. aureus, E. coli, and Salmonella in meat and swab samples was 37.5%, 32.5%, and 7.5%, respectively. In this study, it was observed that all samples collected from butcher shops detected a significant count of spoilage microbes. Hence, adequate sanitary measures should be taken from production to consumption stages.